EVALUASI PENERAPAN GANTI UANG DI DIREKTORAT LALU LINTAS POLDA SULAWESI UTARA - Ardilina, Isma; Runtu, Treesje; Tirayoh, Victorina Z. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Spending treasurer filed SPP-UP the beginning of each fiscal year after the issuance of the Decree on the magnitude Regional Head UP. At the time of Money Supply has been use spending treasurer may submit SPP-GU with a number of different use of Money Supply SPJ which has been passed in a specific time period. PERMENDAGRI N0. 13 of 2006 and PERMEENDAGRI No.55 of 2008 has given a detailed regulation on the administration and preparation of money supply and change of money supply. The purpose of this study was to know implementation of change money of traffic directorate is in compliance with applicable regulation or contrary to existing rules. The analysis method used in this research using descriptive qualitative. The result shows that Traffic Directorate Polda Sulut has made the application of money change in the directorate in accordance with applicable regulation.Keyword: Treasurer, Money Supply, Change Money